2022
DOI: 10.1002/pol.20220121
|View full text |Cite
|
Sign up to set email alerts
|

Poly(hydroxyurethane‐co‐thiourethane)s cross‐linked with disulfide bonds: Synthesis via isocyanate‐free approach, thermomechanical and reprocessing properties

Abstract: Both difunctional five-membered cyclic carbonate (E5CC) and trithiocarbonate (E5CTC) were synthesized via the reactions of diglycidyl ether of bisphenol A (DGEBA) with carbon dioxide (CO 2 ) and carbon disulfide (CS 2 ), respectively. These two monomers were employed to synthesize linear poly(hydroxyurethaneco-mecaptotrithiourethane) [P(HU-co-MTU)] copolymers via the polymerization with an α,ω-diamino-terminated poly(propylene oxide). By controlling the mole ratios of E5CC to E5CTC, the P(HU-co-MTU) copolymers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…Due to their larger and more favorable ring strain, DTCs are more reactive to nucleophiles than their oxygen analogues, i.e., CCs, which enables relatively fast reactions under milder conditions. , Moreover, the amine reacts with the S–C­(S) bond in DTCs by regioselective nucleophilic addition, leading to an enhanced selectivity toward the formation of 100% primary thiol, unlike the reaction with CCs which often leads to 60–70% secondary hydroxyl groups. ,,, We note that a recent study reported polythionourethane synthesized from isothiocyanate and alcohol . The thionourethane linkage also has the sulfur atom at the thiocarbonyl position, with a linkage structure like the linkages in what the research literature has called NIPTUs since 1995. ,,,, However, NIPTUs have additional primary thiol groups that distinguish them from polythionourethanes. Because the naming of these materials as NIPTUs is well established, ,,,, we will refer to our materials as NIPTUs.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Due to their larger and more favorable ring strain, DTCs are more reactive to nucleophiles than their oxygen analogues, i.e., CCs, which enables relatively fast reactions under milder conditions. , Moreover, the amine reacts with the S–C­(S) bond in DTCs by regioselective nucleophilic addition, leading to an enhanced selectivity toward the formation of 100% primary thiol, unlike the reaction with CCs which often leads to 60–70% secondary hydroxyl groups. ,,, We note that a recent study reported polythionourethane synthesized from isothiocyanate and alcohol . The thionourethane linkage also has the sulfur atom at the thiocarbonyl position, with a linkage structure like the linkages in what the research literature has called NIPTUs since 1995. ,,,, However, NIPTUs have additional primary thiol groups that distinguish them from polythionourethanes. Because the naming of these materials as NIPTUs is well established, ,,,, we will refer to our materials as NIPTUs.…”
Section: Introductionmentioning
confidence: 97%
“…The thionourethane linkage also has the sulfur atom at the thiocarbonyl position, with a linkage structure like the linkages in what the research literature has called NIPTUs since 1995. ,,,, However, NIPTUs have additional primary thiol groups that distinguish them from polythionourethanes. Because the naming of these materials as NIPTUs is well established, ,,,, we will refer to our materials as NIPTUs. However, we acknowledge that NIPTUs contain thionourethane linkages with additional primary thiol groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be influenced by the structure and length of the hard segments, which directly determine the physical properties of the polyurethane material. [9][10][11] In order to increase the mobility of the polyurethane matrix, the polyurethane main chain must be modified to ensure a higher degree of vibration and mobility in the macromolecular morphology. 12,13 Traditional polyurethanes are insoluble in water and have a hydrophobic character.…”
Section: Introductionmentioning
confidence: 99%
“…Hard domains formed by self‐organization and physical crosslinks determine the morphology of the phases. This can be influenced by the structure and length of the hard segments, which directly determine the physical properties of the polyurethane material 9–11 . In order to increase the mobility of the polyurethane matrix, the polyurethane main chain must be modified to ensure a higher degree of vibration and mobility in the macromolecular morphology 12,13 …”
Section: Introductionmentioning
confidence: 99%